Synthesis and antimicrobial activity of molecular hybrids based on eugenol and chloramphenicol pharmacophores - Oliveira, Lucas M; Siqueira, Fallon S; Silva, Michelle T; Machado, José V C; Cordeiro, Cleydson F; Diniz, Lívia F; Campos, Marli M A; Franco, Lucas L; Souza, Thiago B; Hawkes, Jamie A; Carvalho, Diogo T (Folia microbiologica, 2023)
In the constant search for new pharmacological compounds, molecular hybridisation is a well-known technique whereby two or more known pharmacophoric subunits are combined to create a new "hybrid" compound. This hybrid is expected to maintain the characteristics of the original compounds whilst demonstrating improvements to their pharmacological action. Accordingly, we report here a series of molecular hybrid compounds based upon eugenol and chloramphenicol pharmacophores. The hybrid compounds were screened for their in vitro antimicrobial potential against Gram-negative and Gram-positive bacteria and also rapidly growing mycobacteria (RGM). The results highlight that the antimicrobial profiles of the hybrid compounds improve in a very clear fashion when moving through the series. The most prominent results were found when comparing the activity of the hybrid compounds against some of the multidrug-resistant clinical isolates of Pseudomonas aeruginosa, methicillin-resistant clinical isolates of Staphylococcus aureus (MRSA) and clinical isolates of rapidly growing mycobacteria.
Keywords: Staphylococcus aureus; Pharmacophore; chloramfenikol; Microbial Sensitivity Tests; farmakofor; antiinfekční látky; eugenol; mikrobiální testy citlivosti; antibakteriální látky; Anti-Infective Agents; Anti-Bacterial Agents; Eugenol; Methicillin-Resistant Staphylococcus aureus; methicilin rezistentní Staphylococcus aureus; Chloramphenicol